Unusual case of urethral steinstrasse following laser cystolitholapaxy - Tsing, Vaite Lisa Marie (BMJ Case Rep, 2017)
Urethral steinstrasse is a rare finding. This case describes a 35-year-old man presenting with urethral steinstrasse 4 weeks following laser cystolitholapaxy of a large bladder stone.